(untitled) (Comunicação & Inovação, 2017)
The purpose of this article is to discuss the productivity of the dispositif’s concept as a methodological operator of research whose theoretical axis is the study of communication in the world of work, considering that the discussion is divided in three parts. First, in the introduction, we discuss concepts of communication and work and of communication in the world of the work. After that, it presents some definitions of dispositif and identify the one with which it deals, as well as the notion of dispositif is discussed from several authors’ perspective, based on a critique of Michel Foucault and adopting the conceptual approach of Dominique Maingueneau. At last, we propose a way of operating the concept of dispositif for communication research in the world of work. In conclusion, we reaffirm the relevance of the communication and work binomial and the contributions of its applications.